Oral Parafunctional Habits in Individuals with The Extravert Personality Type - Ur Rehman, Saeed; Liaqat, Momina; Butt, Hira; Hafiz, Fatima; Qasim, Sharqa; Nauman khan, Amna; Khan, Nauman Rauf (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: To find the association of extraversion personality traits with oral parafunctional habits. METHODOLOGY: A Cross-sectional descriptive study was conducted on 200 individuals in the College of Dentistry, Sharif Medical and Dental College, Lahore, over 5 months from July to November 2021. Data was collected using a pre-validated medical questionnaire and a ten-item personality inventory scale (TIPI). The sampling technique used was Convenience sampling. A sample size of 200 was calculated with the help of WHO sample size determination software. RESULTS: There was a statistically significant difference in the scores of extraversion personality traits across the oral parafunctional habit group of nail-biting (p= 0.007). In contrast, that for tooth grinding (0.114), tooth clenching (0.076), biting hard objects (0.74) and chewing gum (p= 0.659) was non-significant. The highest mean rank score for the personality trait of extraversion was found in individuals who strongly agreed to have a habit of nail-biting (129.23), tooth grinding (153.63), and tooth clenching (142.61) and biting hard objects (12.07). The highest mean rank score for the parafunctional habit of chewing gum (107.28) was found in individuals who strongly disagreed with having the habit. CONCLUSION: The highest mean rank score for the personality trait of extraversion was found in individuals who strongly agreed to have a habit of nail-biting, tooth grinding, tooth clenching and biting hard objects. The highest mean rank score for the parafunctional habit of chewing gum was found in individuals who strongly disagreed with having the habit.